Innovations in organizational IT specification and standards development - Jakobs, Kai, 1957-.; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
'This book provides advancing research on all current aspects of IT standards and standardization'--Provided by publisher.
Innovative or indefensible? an empirical assessment of patenting within standard setting / Anne Layne-Farrar -- Assessing the link between standards and patents / Anne Layne-Farrar, A. Jorge Padilla -- Interpreting and enforcing the voluntary FRAND commitment / Roger G. Brooks, Damien Geradin -- The standards war between ODF and OOXML: does competition between overlapping ISO standards lead to innovation? / Tineke M. Egyedi, Aad Koppenhol -- The battle within: an analysis of internal fragmentation in networked technologies based on a comparison of the DVB-H and T-DMB mobile digital multimedia broadcasting standards / H{uA86B}on Ursin Steen -- Implementing standardization education at the national level / Henk J. de Vries -- The role of standards in engineering education / Todor Cooklev -- Where are you? consumers' associations in standardization: a case study on Switzerland / Christophe Hauert -- The INTERNORM Project: bridging two worlds of expert- and lay-knowledge in standardization / Jean-Christophe Graz, Christophe Hauert -- Beyond the'point of no return': constructing irreversibility in decision making on the Tetra standard in Dutch emergency communication / Anique Hommels, Tineke M. Egyedi -- The significance of government's role in technology standardization: two cases in the wireless communications industry / DongBack Seo -- An exploratory analysis of the relationship between organizational and institutional factors shaping the assimilation of vertical standards / Rub{u296E} A. Mendoza, T. Ravichandran -- Analysis and validation of learning technology models, standards and specifications: the reference model analysis grid (RMAG) / Jan M. Pawlowski, Denis Kozlov -- Key challenges in the design of learning technology standards: observations and proposals / Adam R. Cooper -- Community-driven specifications: XCRI, SWORD, and LEAP2A / Scott Wilson -- Concepts and standardization in areas relating to competence / Simon Grant, Rowin Young -- Application profiles and tailor-made conformance test systems / Ingo Dahn, Sascha Zimmermann -- A data model for describing and exchanging personal achieved learning outcomes (PALO) / Jad Najjar ... [et al.].
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed September 20, 2012).
Keywords: Information technology -- Standards; Standardization; Conformity assessment; Economics of standardization; Intellectual property rights; Open source and standardization; Economic development; Regulation; Public policy; Public sphere; Standards for information infrastructures; Technological innovation